Strengthening Faculty News Governance through a Collaborative Cross-Program SOP - Noprita Herari; E. Nugrahaeni Prananingrum (Journal of Indonesian Society Empowerment, 2026)
This community service activity aimed to strengthen faculty news and public relations information governance at the Faculty of Social Sciences and Law, Universitas Negeri Jakarta, through the development of a Standard Operating Procedure (SOP) based on cross-program collaboration. The main issue faced by the partner was the absence of a standardized workflow for news submission, verification, editing, approval, and publication, causing information from study programs to remain scattered across internal WhatsApp groups, incomplete, and not fully represented on the faculty’s official media channels. This activity employed a qualitative-participatory approach through digital media inventory, observation of the existing publication workflow, benchmarking with seven faculties, interviews with faculty leaders and public relations managers, and a Focus Group Discussion with the Chair and Vice Chair of FISHMed. The activity resulted in two SOPs: one for news submissions from 15 study programs and another for activities directly covered by FISHMed. The SOPs were supported by a press release form, a standardized submission flow, role separation between website and social media teams, five news categories, and publication narratives linked to SDGs, IKU, and faculty branding. This activity demonstrates that a faculty news SOP can serve as a practical instrument to improve accountability, equitable news coverage, information service quality, and institutional reputation. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat tata kelola berita dan informasi kehumasan Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, melalui penyusunan Standard Operating Procedure (SOP) berbasis kolaborasi lintas program studi. Permasalahan utama yang dihadapi mitra adalah belum terstandarnya alur pengajuan, verifikasi, penyuntingan, persetujuan, dan publikasi berita, sehingga informasi dari program studi sering tersebar melalui WhatsApp internal, belum lengkap, dan belum seluruhnya terpublikasi pada media resmi fakultas. Metode kegiatan menggunakan pendekatan kualitatif-partisipatif melalui inventarisasi media digital, observasi alur publikasi berjalan, benchmarking dengan tujuh fakultas, wawancara dengan pimpinan fakultas dan pengelola kehumasan, serta Focus Group Discussion dengan Ketua dan Wakil Ketua FISHMed. Hasil kegiatan menghasilkan dua SOP, yaitu SOP publikasi berita dari 15 program studi dan SOP publikasi kegiatan yang diliput langsung oleh FISHMed. SOP ini dilengkapi dengan formulir press release, alur pengajuan terstandar, pembagian peran website dan media sosial, lima kategori berita, serta penguatan narasi berbasis SDGs, IKU, dan branding fakultas. Kegiatan ini menunjukkan bahwa SOP berita fakultas dapat menjadi instrumen praktis untuk meningkatkan akuntabilitas, pemerataan coverage, kualitas layanan informasi, dan reputasi kelembagaan fakultas.